2003
DOI: 10.1074/jbc.m208968200
|View full text |Cite
|
Sign up to set email alerts
|

Tn5 Transposase Active Site Mutations Suggest Position of Donor Backbone DNA in Synaptic Complex

Abstract: Tn5 transposase (Tnp), a 53.3-kDa protein, enables the movement of transposon Tn5 by a conservative mechanism. Within the context of a protein and DNA synaptic complex, a single Tnp molecule catalyzes four sequential DNA breaking and joining reactions at the end of a single transposon. The three amino acids of the DDE motif (Asp-97, Asp-188, and Glu-326), which are conserved among transposases and retroviral integrases, have been shown previously to be absolutely required for all catalytic steps. To probe the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Piv E59D and Piv D101E exhibit very low levels of recombination, and generating a DDE-, versus DED-, motif in the linear amino acid sequence of Piv (Piv E59D/D101E and Piv E59D/D104E) did not yield an active recombinase. These results are consistent with substitution analyses of the DDEmotif in Tn5 Tnp and the DEDD-motif in the Holliday junction resolvase RuvC (26,28). These studies showed that substitution of catalytic residues with nonacidic amino acids eliminates recombination activity, but interchanging aspartic acid and glutamic acid residues at catalytic positions (other than the first aspartic acid) is tolerated to give low levels of in vitro catalytic activity.…”
Section: Discussionsupporting
confidence: 78%
“…Piv E59D and Piv D101E exhibit very low levels of recombination, and generating a DDE-, versus DED-, motif in the linear amino acid sequence of Piv (Piv E59D/D101E and Piv E59D/D104E) did not yield an active recombinase. These results are consistent with substitution analyses of the DDEmotif in Tn5 Tnp and the DEDD-motif in the Holliday junction resolvase RuvC (26,28). These studies showed that substitution of catalytic residues with nonacidic amino acids eliminates recombination activity, but interchanging aspartic acid and glutamic acid residues at catalytic positions (other than the first aspartic acid) is tolerated to give low levels of in vitro catalytic activity.…”
Section: Discussionsupporting
confidence: 78%
“…However, AGO2 and -3 differ from the other AGOs in that they have an additional aspartate as the third coordinating residues in place of the conserved histidine. This third carboxylic acid residue is not likely to impair Slicer activity because two other related enzymes, RNaseH1 and Tn5 integrase, can use aspartate efficiently in that position (13,59,60). Most of the AGO proteins, also like hAGO2, have a conserved histidine at the equivalent of AGO1 position 798, and it is likely that they selectively recruit siRNAs or a subset of miRNAs and use them as guides in RNA cleavage reactions.…”
Section: Selective Srna Recruitment and Slicer Activity In Other Arabmentioning
confidence: 99%
“…The published cocrystal structure predicts the existence of five different Tnp regions that make ES contacts; two regions form cis contacts, and three regions form trans contacts (9). Three of these regions have been extensively studied in other work (2,5,16,17,19,25,27,30,31). In this communication we present analyses of the remaining two regions (the cis contact region from residue 342 to 348 and the trans contact region from residue 438 to 445) and verify, through genetics and biochemistry, that these regions play an important role in synaptic complex formation.…”
Section: Discussionmentioning
confidence: 99%